Shock and release of tantalum studied via molecular dynamics and femtosecond x-ray diffraction - Heighway, PG (2020)
The response of solid matter to shock compression is complexified considerably by its strength, or its ability to withstand shear stress. Strength is challenging to measure experimentally under shock conditions and even harder to model, due to its being an extremely complicated function of the loading conditions. Our understanding of material strength and the way it manifests under dynamic loading thus remains, to a great extent, incomplete. This work presents studies of two phenomena arising from strength under the conditions of shock compression and release by means of multimillion-atom molecular dynamics simulations and femtosecond x-ray diffraction. The role of shock-induced grain interactions is first explored via simulations of elementary polycrystals. Such interactions are found to control the plasticity mechanisms activated under shock compression and the limiting shear stress state to which the polycrystal settles in the wake of the shock. A combined experimental-computational study of plastic-work heating under the conditions of shock release is then presented. An algorithm for extracting the temperature of released samples from their diffraction image is derived and verified on synthetic data. When applied to experimental data, the algorithm shows that the temperatures of shock-released tantalum foils vastly exceed those expected from a conventional isentropic release. The underlying microphysical processes responsible for the heating are then interrogated via large-scale simulations of crystals under shock and release. A heat equation is used to identify plastic-work heating owed to the sample’s exceptional strength during its rapid release as the culprit, thus challenging the conventional assumption that shock release is a universally isentropic process.